The impact of magnetic fields on the chemical evolution of the supernova-driven ISM - Pardi, Anabele-Linda; Glover, Simon; Klessen, Ralf S. (Arxiv, 2016)
We present three-dimensional magneto-hydrodynamical simulations of the self-gravitating interstellar medium (ISM) in a periodic (256 pc)$^3$ box with a mean number density of 0.5 cm$^{-3}$. At a fixed supernova rate we investigate the multi-phase ISM structure, H$_{2}$ molecule formation and density-magnetic field scaling for varying initial magnetic field strengths (0, $6× 10^{-3}$, 0.3, 3 $μ$G). All magnetic runs saturate at mass weighted field strengths of $\sim$ 1 $-$ 3 $\m but the ISM structure is notably different. With increasing initial field strengths (from $6× 10^{-3}$ to 3 $μ$G) the simulations develop an ISM with a more homogeneous density and temperature structure, with increasing mass (from 5% to 85%) and volume filling fractions (from 4% to 85%) of warm (300 K $<$ T $<$ 8000 K) gas, with decreasing volume filling fractions (VFF) from $\sim$ 35% to $\sim$ 12% of hot gas (T $> 10^5$ K) and with a decreasing H$_{2}$ mass fraction (from 70% to $<$ 1%). Meanwhile the mass fraction of gas in which the magnetic pressure dominates over the thermal pressure increases by a factor of 10, from 0.07 for an initial field of $6× 10^{-3}$ $\m to 0.7 for a 3 $\m initial field. In all but the simulations with the highest initial field strength self-gravity promotes the formation of dense gas and H$_{2}$, but does not change any other trends. We conclude that magnetic fields have a significant impact on the multi-phase, chemical and thermal structure of the ISM and discuss potential implications and limitations of the model.
Gesehen am 25.10.2017